Video-Based Learning on PPKn Education with the Topic of Symbols and Meanings of Pancasila - Akhmad AR, Anggun Rimada; Bayu, Gede Wira; Sudatha, I Gde Wawan (Universitas Pendidikan Ganesha, 2021)
Learning activities have not been carried out optimally. The learning media used is only fixed on one source of textbooks, so students have difficulty understanding the material. In addition, teachers only teach using the assignment and lecture methods. This study aims to develop learning media in the form of videos to assist students in learning. This type of research is development research with the model used is ADDIE. The methods used in collecting data are observation, interviews, and questionnaires. The instrument used in collecting data is a questionnaire. The subject of this research is Civics learning video media on the topic of symbols and meanings of the Pancasila precepts, in this study the data analysis technique used in this development research was using qualitative descriptive statistical analysis techniques and quantitative descriptive statistics. The results of the research are the results of the expert test of the content of the subjects developed to get the results of 4.84 with very good qualifications, the learning design experts get the results of 4.22 with very good qualifications, the test results from the learning media experts get the results of 4.30 with the qualifications very good. The results of the practitioner test got a result of 4.58 with very good qualifications, the results of the limited trial got a result of 4.79 with very good qualifications. It can be concluded that the media developed is feasible to be applied in learning. The implication of this research is that the developed media can make it easier for students to understand Civics subject matter, especially the topic of symbols and meanings of the Pancasila precepts.